Questionnaire on the Current Status and Awareness of Palliative Medicine by Community Cooperation Pharmacies - Keigo Nagatani; Mayu Nakahara; Sachiko Omotani; Michiaki Myotoku (MDPI AG, 2024)
Community cooperation pharmacies are equipped to prepare narcotics and sterile injectable drugs for palliative medicine at home for cancer pain and end-of-life care; however, to the best of our knowledge, the actual status of the system to provide palliative medicine at home has not yet been examined. Therefore, in this study, given that home palliative medicine is one of the accreditation criteria for community cooperation pharmacies, a questionnaire survey was conducted among managing pharmacists engaged in community cooperation pharmacies to investigate the actual status of the system to provide appropriate services, mainly pain management, to patients who need home palliative medicine. An analysis of responses to the questionnaire showed that pharmacists working in community cooperation pharmacies had a high level of understanding of the proper use of rescue doses of medical narcotics and patient guidance. Pharmacists with experience in sterile and injection preparations also had a high level of understanding of palliative medicine. On the other hand, they had a low level of understanding of the WHO method for cancer pain treatment and appropriate suggestions for opioid switching. These results indicate that the creation of learning opportunities, such as training on injectables and prescription designs, for pharmacists in community cooperation pharmacies is one of the measures that may improve their understanding of palliative medicine.